Children Citizenship Status of Acehnese-Rohingya Mixed Marriage in Aceh: Maqāṣid Sharī’ah Perspective - Husna, Nurul; Asy Ari, M Khoirul Hadi al; Suryani, Sitti; Anizar, Anizar; Juliandi, Budi (Al-Ahkam, 2024)
Citizenship status is important in mixed-country marriages. This research explores the important issue of citizenship in mixed marriages between Rohingya refugees and local Acehnese. The research aims to examine whether the citizenship status of the children of such marriages is based on the doctrine of revival or habitual residence. Using a literature review method with a descriptive qualitative approach, this research investigates the concepts and legal implications surrounding citizenship status in such marriages. The findings of this study reveal that the citizenship status of children born from Acehnese-Rohingya marriages follows habitual residence, even though their Rohingya parents adhere to the doctrine of revival The legal status of these children is subject to the Indonesian marriage law system. This is in line with Jasser Auda’s concept of maqāṣid sharī’ah because it prioritizes aspects of the benefit of these children. This research provides important insights into the issue of citizenship In Acehnese-Rohingya marriages and offers valuable meaning for understanding the dynamics of citizenship in these marriages.